Validation of a module of constructive strategies to improve reading comprehension in english - EBA - Alvarado Flores, María Julia (2019)
The purpose of this research is to demonstrate the effectiveness of the use of the constructivist strategy to improve reading comprehension in the English language in students of Alternative Basic Education (EBA) of the Ministry of Education of Peru. The application of this strategy allows the student to get involved with the text, since it gathers his previous experiences as a reader, as well as his daily life; pushing it to put together new concepts, facilitating in this way to understand the texts it reads. The "A busy day in the office" Entry and Exit Test is applied, which has achieved the principles of validity and reliability, before starting the experience. A sample of 32 first-year students of the CEBA "Bartolomé Herrera", 16 of the "A" section, control group and 16 of the "B" section of the experimental group was selected. The ages of the students range from 16 to 29 years; According to the Dakar Objectives (2012), the greatest challenge of education lies in the access and completion of disadvantaged or marginalized groups. This work summarizes the solution to a problem: that students understand when they read, increase their capacity for retention, deduction-induction, opinion and recreation (Solé, 2004). The application of the strategies before, during and after the reading allows the students to respond satisfactorily to the literal, inferential and critical-evaluative questions. In addition, the experimental group demonstrates more perseverance when working in class when the topics are linked to their needs and interests. It is a significant instrument, which includes the approaches of a Constructivist methodology, through which the reader interacts with the text, mentally arming ideas and interpreting those (Pinzás, 2012). In the annex a reading card is considered, the image and questions in each one of the levels of reading comprehension; as well as other activities that made it possible for students to understand and work on the texts.